2020
DOI: 10.1080/01490451.2020.1801907
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acid Production by Penicillium oxalicum on Physicochemical Properties of Bauxite Residue

Abstract: Large-scale discharge of bauxite residue, an alkaline, saline and nutrientdeficient waste material produced in the process of alumina production, has created extreme environments that are challenging to restore. Microbial pathways are found to play a critical role in the rehabilitation of these residues. In this study, Penicillium oxalicum, an alkaliresistant acid-producing fungus screened from bauxite residue disposal sites, was used to examine its effectiveness for restoration of bauxite residue. By comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Correlation analysis indicated that the medium pH was significantly negatively correlated with the secretion of total organic acid content ( Table S4 ). These results further verified that acid fermentation was the major mechanism for decreasing the pH of the medium, which is consistent with previous reports [ 20 , 29 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Correlation analysis indicated that the medium pH was significantly negatively correlated with the secretion of total organic acid content ( Table S4 ). These results further verified that acid fermentation was the major mechanism for decreasing the pH of the medium, which is consistent with previous reports [ 20 , 29 ].…”
Section: Resultssupporting
confidence: 93%
“…However, most previous studies emphasized the importance of amendments, and the roles of microorganisms in reducing the pH of BR was ignored to a certain extent. With the rapid development of biotechnology, the critical role of microorganisms in decreasing the pH of BR has been recognized [ 20 , 29 ]. Some exploratory studies on reducing the pH of BR by microorganisms have been conducted in recent years, including bacterial, fungal and microbial-rich amendments [ 33 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…P. oxalicum was cultivated according to the previously mentioned . The straw was added to a 2% v/v H 2 SO 4 solution at a ratio of 1:5 (w/v) and washed with deionized water more than 3 times.…”
Section: Methodsmentioning
confidence: 99%
“…P. oxalicum was cultivated according to the previously mentioned. 29 The straw was added to a 2% v/v H 2 SO 4 solution at a ratio of 1:5 (w/v) and washed with deionized water more than 3 times. The treated straw was then mixed with P. oxalicum liquid at a ratio of 1:2 (w/v) to serve as a microbial inoculant (details in Supporting Information 2.1).…”
Section: Methodsmentioning
confidence: 99%
“…This short-chain saturated triglyceride is a major product of amino acid and dicarboxylic acid metabolism (consuming glycerol as an ideal source) and a precursor of carboxylic acid metabolism [36,38]. Microbes can convert propionic acid to propionyl-CoA and utilize it for carboxylic acid (including gluconic, galactaric, and glucuronic acid) production [36,39]. Significantly increased levels of propionic acid were only observed in IP treatment (Figures 4 and 6), suggesting that amino acids were used and converted into gluconic acid in the IP treatment, which was consistent with the lack of a significant increase in the amino acids methionine, serine and tyrosine involved in propionic acid production and the increase in glyceric acid (FC > 2) in IP treatments (Figure 4) [40].…”
Section: Metabolism Associated With Propionic Acidmentioning
confidence: 99%